Parentalidade "prematura": um estudo sob a ótica da teoria das representações sociais - Barros, Sibelle Maria Martins de (2007)
The way couples react and cope with the premature birth of a child depends on how they comprehend and live this new experience. This, in turn, is associated to the meanings assigned to motherhood and fatherhood, or the representations of motherhood and fatherhood. Stemming from this presumption, the present research aimed to understand, under the light of Social Representation Theory (SRT), the experience of couples whose premature newborns had been hospitalized in a Neonatal Intensive Care Unit (NICU). Individual interviews with a semi structured script were performed with 20 couples whose children were under NICU treatment in Recife (Pernambuco state, Brazil). The interview script covered the following themes: pregnancy/parturition; newborn diagnostics; son; motherhood, fatherhood, impacts of the experience on conjugal relationship and coping. For data analysis was chosen the methodology proposal of the Grounded Theory, which allows the formulation of a theory about the data through the construction of structures on identified phenomena throughout the analysis process. Three phenomena emerged from the data analysis: Coming to contact with a high-risk situation; Coping daily with the pain; and Learning to be premature father and mother. Such phenomena allowed comprehending the dynamics of social representations, mainly on motherhood and fatherhood, in the experience of the studied couples. The social representations acted in the interpretation of the new reality; provided and were influenced by feelings and emotions of fathers and mothers; and guided the coping strategies. At the same time, these representations suffered constant influences of the context, the established relations in it, and of the coping strategies adopted by the couples. The present psychosocial research alerts to the importance of considering the role of the sociocultural context in the investigation of the experiences lived by the subjects regarding health. It is also intended to subsidize intervention proposals aimed to “premature” fathers and mothers with the objective of facilitating coping with the situation and learning while exercising the “premature” parenthood.